Pour une histoire de l’usage médical des stupéfiants : état des lieux et perspectives - Zoë Dubus (Histoire, Médecine et Santé)
Historiography in general, and that produced in France in particular, traditionally presents narcotics as uniformly dangerous substances. This systematic focus on addiction, deviance, and risks for users or society, observable for instance in the majority of historical dissertations on the topic of psychoactive substances, obscures the existence of research fields concerning their therapeutic uses—which were, in fact, the original reason for their integration into Western practices. This article will thus offer an analytical and critical overview of historical research that examines the “career” of narcotics as medicines, a field primarily dominated on the one hand by Anglo-American literature, and on the other by authors from medical professions who are not trained in historical methodology. Additionally, it will attempt to highlight various research avenues that remain to be explored in order to deepen our understanding of the medical uses of these controversial substances.